Collapse of a transport current in hard superconductors - Baltaga, I.V.; Makarov, N.М.; Yampolskii, V.A.; Fisher, L.M.; Voloshin, I.F. (Физика низких температур, 1995)
A phenomenon of compression of a transport current I by an external ac magnetic field in hard superconductors being in the critical state is studied both theoretically and experimentally. This phenomenon occurs in a forceless configuration when the ac field and the transport current are parallel. The collapse takes place owing to forcing out the transport current by shielding currents flowing inside a surface region of a sample. Using the Hall probe we have directly observed such stratification of the currents with different orientations. The transport current tube contracts to the sample axis as the ac amplitude increases and occupies the whole sample core at some threshold amplitude Ht. As a result, the superconductor goes to the resistive state. A dependence of Ht on I is analyzed both theoretically and experimentally. It is shown, that the collapse in superconducting rings is accompanied by complex relaxation processes. The mechanism of decay of the circular current in rings under the action of an ac signal is investigated in detail. An application of the collapse to test the homogeneity of the critical current capability of superconductors is discussed.